Corpus. - Nancy, Jean-Luc (Perspectives in continental philosophy., 2008)
How have we thought 'the body'? How can we think it anew? This title incorporates the body of mortal creatures, the body politic, the body of letters and of laws, and the 'mystical body of Christ'. It offers us an encyclopedia and a polemical program - reviewing classical takes on the "corpus" from Plato, Aristotle, and Saint Paul to Descartes.